Youth, Identity, and Romantic Relationships: Negotiating Uncertain Futures in Pontianak, West Kalimantan - Wenty Marina Minza, Wenty (2012)
Romantic relationship is often viewed as a prelude to marriage, but it may also be seen as a form of youth cultures of sexuality. As prelude to marriage, romantic relationships function as part of the growing up process. On the other hand, when it takes form in youth cultures of sexuality, it functions as a part of forming a youth identity. I argue that long term relationships are a form of negotiation that young people undertake to strategize between the tensions of growing up and being young. Romantic relationships are not seen as a prelude to marriage, but neither is it seen as part of a youth culture of sexuality. Instead, they think of having long term relationships, meaning that they want the relationship to last even without the certainty of marriage. It means that long term relationship is similar to youth cultures of „waiting‟. Unlike youth cultures of sexuality that focuses on the present identity and status, youth cultures of waiting involve structural constraints that inhibit young people to enter marriage.